2002
DOI: 10.1128/cdli.9.3.550-557.2002
|View full text |Cite
|
Sign up to set email alerts
|

CD8α-Deficient Mice Are Highly Susceptible to 5-Fluorouracil-Induced Lethality

Abstract: Intestinal intraepithelial lymphocytes (i-IEL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…We speculate that IgA production could be negatively affected by a decrease in the number of CD21+ B cells in ileal PP and colon LGC, which are the main reservoirs of B cells in the intestine. This impairment in the immunological barriers of the intestine may lead to lethal translocation of bacteria from the intestinal lumen to the bloodstream and distant organs [7,8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that IgA production could be negatively affected by a decrease in the number of CD21+ B cells in ileal PP and colon LGC, which are the main reservoirs of B cells in the intestine. This impairment in the immunological barriers of the intestine may lead to lethal translocation of bacteria from the intestinal lumen to the bloodstream and distant organs [7,8] .…”
Section: Discussionmentioning
confidence: 99%
“…The damage includes perturbed brush-border hydrolase activity [5] , reduced mucosal DNA, RNA and protein contents [1] , blunted villus height and crypt depth, and decreased proliferation and increased apoptosis of crypt cells [6] . Additionally, 5-FU impairs immunocompetent cells leading to lethal translocation of bacteria from the intestinal lumen to the bloodstream and distant organs [7,8] . These cellular changes ultimately result in a clinical syndrome of diarrhea, intestinal blood loss, dehydration, impaired nutrition, disseminated infections and weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…They speculated that the direct stimulation of i-ECs by intestinal microflorae via MyD88-dependnet TLR signaling induces cytoprotective cytokines and proteins, including IL-6 and heat shock protein, which result in steady state intestinal epithelial homeostasis. We previously reported that CD8␣ Ϫ/Ϫ mice showed high susceptibility to 5-fluorouracil-induced intestinal injury (40), suggesting that CD8␣␣ i-IELs are important for intestinal homeostasis. Therefore, we suggest that impairment of development, differentiation, and maintenance of CD8␣␣ and TCR␥␦ i-IELs in MyD88…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic cells and normal epithelial cells of the gastrointestinal tract are susceptible to 5-FU induced cytotoxicity producing severe leukopenia and intestinal toxicity leading to lethal translocation of intestinal microflora [21][22][23][24] . In general our findings are in line with previous studies that have reported that systemic 5-FU administration causes epithelial barrier dysfunction of the rat intestine [25] , and causes bacterial translocation [26] .…”
Section: Discussionmentioning
confidence: 99%